2017
DOI: 10.1097/md.0000000000008169
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis after surgery for intertrochanteric fracture in elderly patients with clopidogrel treatment

Abstract: Choice of surgical approach in patients under clopidogrel treatment is controversial. Intertrochanteric fractures are common in the elderly, who also suffer from a number of comorbidities.The aim of this study is to assess the prognosis of elderly patients with clopidogrel treatment after surgery for intertrochanteric fracture.This was a cohort study of 238 elderly patients who underwent proximal femur intramedullary nailing for intertrochanteric fracture between January 2012 and December 2013 at the Geriatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…However, a higher drop in Hb is expected in those on dual APA therapy [ 773 , 774 ]. In contrast, in another study, patients who underwent surgery for intertrochanteric fracture while on clopidogrel had a poorer prognosis compared with controls: intraoperative blood transfusion, ICU and hospital stays and 1-year mortality were higher, despite having the same rate of postoperative complications [ 775 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a higher drop in Hb is expected in those on dual APA therapy [ 773 , 774 ]. In contrast, in another study, patients who underwent surgery for intertrochanteric fracture while on clopidogrel had a poorer prognosis compared with controls: intraoperative blood transfusion, ICU and hospital stays and 1-year mortality were higher, despite having the same rate of postoperative complications [ 775 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [ 19 ] reported that continuation of preoperative clopidogrel for patients undergoing intramedullary nailing for an intertrochanteric fracture resulted in higher chances of intraoperative transfusion, increased ICU admission and total duration of hospitalization, and a lower one-year survival rate, leading to poor prognosis. Our results were consistent with those of Zhang et al in terms of total transfusion volume and ICU admission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30-50% of patients with hip fractures have cardiovascular comorbidity that requires antithrombotic treatment (antiplatelet, vitamin K antagonists (VKA) or direct oral anticoagulants (DOACs) [126]. Early surgery (within 48 h) has been proven to reduce complications and mortality at 30 days and 1 year in hip fracture patients even if receiving antithrombotic treatment [127][128][129], although these drugs can potentially interfere with regional anaesthesia or increase perioperative bleeding. Choosing the optimal moment for surgery should thus balance thrombotic and bleeding risks with the risks of delayed surgery and the benefits and risks of spinal anaesthesia.…”
Section: Perioperative Antithrombotic Managementmentioning
confidence: 99%